What Have We Not Learned from the Convergence Debate? - Leone Leonida (Mathematics, 2023)
We argue that the alternative hypotheses about cross-country convergence dynamics, namely the Conditional Convergence Hypothesis, Absolute Convergence Hypothesis, and Club Convergence hypothesis, build upon different modelling choices and answer different empirical questions. Hence, results favoring one hypothesis are not necessarily evidence against the other hypotheses. We apply several modelling approaches to a sample of world economies to support our argument, and present empirical evidence that yields controversial conclusions if the hypotheses about convergence are taken as competing. However, the controversy disappears as we note that there are neither theoretical nor empirical reasons to take evidence in favor of the Absolute Convergence Hypothesis as necessarily being against the Club Convergence Hypothesis, and vice versa. We present results for the world economies where the two processes co-exist. We conclude by arguing that when analysis is conducted at the regional level, the two processes are more likely to co-exist because regions share the same institutions, culture, natural resources, and other fundamental causes of growth. Consequently, a test for convergence that studies whether clusters converge or diverge once eventually emerged in the distribution of incomes is still needed. Finally, we argue that to study convergence dynamics, it is necessary to model relationships between economies.